Report from Alaska - Jack Cadigan (Journal of Research in Rural Education, 1993)
Formal "distance learning" has been a way of life for many of Alaska's youth since the inception over 50 years ago of a state school providing correspondence education. As a teacher in this school for the past halfdozen years, I have learned first-hand the advantages and disadvantages of this mode of education. I also have gained direct insight into the value of modem technology in distance learning.